Effective Ways Of Teaching Contextualized Grammar In English Class - Ruziev Khusniddin Bakhritdinovich (Academia One, 2024)
This article deal with effective ways of teaching contextualized grammar in English classes. This article are discussed different types of communicative grammar games
Keywords: contextualization; authentic texts; interactive grammar